Bispecific Antibodies in Lung Cancer: A State-of-the-Art Review - Atulya Aman Khosla; Karan Jatwani; Rohit Singh; Aswanth Reddy; Ishmael Jaiyesimi; Aakash Desai (MDPI AG, 2023)
Bispecific antibodies have emerged as a promising class of therapeutics in the field of oncology, offering an innovative approach to target cancer cells while sparing healthy tissues. These antibodies are designed to bind two different antigens, enabling them to bridge immune cells with cancer cells, resulting in enhanced tumor cell killing and improved treatment responses. This review article summarizes the current landscape of bispecific antibodies in lung cancer, including their mechanisms of action, clinical development, and potential applications in other solid tumor malignancies. Additionally, the challenges and opportunities associated with their use in the clinic are discussed, along with future directions for research and development in this exciting area of cancer immunotherapy.